(untitled) (International Journal of Engineering and Computer Science, 2014)
Transmitting huge amount of unlawful or illegal data through the internet is the main motivation to develop this efficient cyber forensic tool. The proposed tool was developed with the help of image mining system and neural network concepts. This paper also describes the main requirements of cyber forensics with respect to image mining system and our proposed tool can be trained by using neural network application to identify intended objects in the scenes. End Users or forensic investigators can use our tool through an algorithm for training, searching and querying